Evaluating the Ultimate Performance of Pylon-Head Joints with Numerical Analysis - Salah, Wael A.; Darweesh, Moustafa S. (Engineering, Technology & Applied Science Research, 2024)
This study presents a comprehensive Finite Element (FE) model of the multiple-cable-to-pylon head joint within a specific cable roof structure. The analysis focuses on the upper part of the pylon substructure, particularly the pylon head joint, to examine its localized behavior under a set of internal forces derived from a simplified FE model. The steel tubular components of the pylon substructure were precisely simulated using thin shell elements. The designers of this particular roof structure proposed two solutions for reinforcing the pylon-head joint, while an additional novel strengthening technique was introduced, aimed at enhancing the joint’s performance. These three strengthening methods, along with the original design joint, were modeled numerically, and the joint’s effectiveness was assessed. The findings of the analysis indicate that the newly proposed strengthening technique exhibits greater potential for stiffening the considered pylon-head joint compared to the other introduced solutions. The study concludes with significant insights relevant to practical applications.